Arsenic speciation in environmental multimedia samples from the Youngsan River Estuary, Korea: A comparison between freshwater and saltwater. (June 2018) - Hong, Seongjin; Choi, Sung-Deuk; Khim, Jong Seong
Abstract: Differences in the distribution, partitioning, and bioaccumulation characteristics of arsenicals between freshwater and saltwater systems remain poorly understood. To determine the characteristics of distribution and behavior of arsenicals, multimedia environmental samples including water, suspended particles, zooplankton, sediments, and porewater were collected from inner (five sites, freshwater) and outer (five sites, saltwater) regions of the estuary dike of the Youngsan River Estuary in South Korea (Nov., 2012). Six organic and inorganic forms of As were separated and measured using HPLC–ICP/MS equipped with an anion exchange column. Concentrations of arsenicals in water samples of the inner region (mean = 1.5 μg As L −1 ) were significantly lower than in those of the outer region (mean = 5.2 μg As L −1 ). Conversely, concentrations of As in suspended particles in the inner region (mean = 14 μg As g −1 ) were much greater than in the outer region (mean = 5.7 μg As g −1 ). The field-based distribution coefficient (Kd ) for As depended strongly on salinity; relatively greater Kd values were found in freshwater compared with saltwater. The As V was found to be the major form of As in all water and particle samples in both inner and outer regions. The zooplankton species were significantly distinguishable between the inner and outer regions; cladocerans were the most dominant species in freshwater and cyclopoida were predominantly found in saltwater. The As concentrations in zooplankton were shown to be particle-concentration dependent, suggesting that dietary exposure plays a substantial role in the bioaccumulation of As. Inorganic arsenicals, such as As V and As III were the most dominant forms found in zooplankton. Partitioning behavior of As between porewater and sediments was similar to that in water–particle distributions. The results of the present study enhance the understanding of As biogeochemistry in river and estuarine environments. Graphical abstract: Image 1 Highlights: Multimedia distributions of As were distinguished between freshwater and saltwater. As V was a major form in the water column, while As III was predominant in sediments. Kd values of As were significantly greater in freshwater than those in saltwater. As bioaccumulation in zooplankton showed a particle-concentration dependent manner. Salinity and adsorption onto SPM are crucial factors influencing As biogeochemistry. Abstract : "Salinity and thereby adsorption characteristics onto SPM are crucial factors affecting As biogeochemistry in freshwater and estuarine areas."